Contextual, social and individual factors as barriers and facilitators for healthcare access of trans women: a community perspective (Actualizaciones en Sida e Infectología, 2018)
Background: Transgender women (TGW) are vulnerable to several health problems, including HIV and other STDs, which significantly reduces their life expectancy. Therefore, there is an urgent need to understand factors affecting access to healthcare.Methods: A qualitative study was conducted among TGW living in rooming houses (TRH) in Buenos Aires. The objective of the study was to explore contextual, social and individual barriers and facilitators to access healthcare, particularly HIV services, and the acceptability of interventions. Two focus groups and five interviews were conducted in three TRH.Results: Contextual barriers described were the limited number of appointments and long waiting hours. Social obstacles included health workers’ stigma and discrimination and blaming of TGW for their health burdens, as well as HIV stigma within TGW groups. Most important facilitator were inclusive services. Individual barriers were self-exclusion and anticipated stigma, resulting in high rates of self-medication and industrial silicone injection. Peers play an important role by accompanying others TGW to healthcare. While reporting similar problems, TGW recommended different interventions according to their THR profile.Conclusions: As the stigma and discrimination is the most important barrier, it is imperative to ensure awareness of transgender issues for all personnel of healthcare services. It is necessary to implement a wide range of strategies in health facilities, and evaluate the community acceptance of domiciliary interventions, in order to respond to the different demands of this population.
Keywords: Transgender persons; Health Services Accessibility; HIV